Lactic acidosis incidence with metformin in patients with type 2 diabetes and chronic kidney disease: A retrospective nested case‐control study. Issue 1 (17th July 2020) - Alvarez, Carlos A.; Halm, Ethan A.; Pugh, Mary Jo V.; McGuire, Darren K.; Hennessy, Sean; Miller, Richard T.; Lingvay, Ildiko; Vouri, Scott M.; Zullo, Andrew R.; Yang, Hui; Chansard, Matt; Mortensen, Eric M.
Abstract: Objective: Compare rates of lactic acidosis (LA) among metformin‐exposed and unexposed patients with type 2 diabetes mellitus and varying degrees of chronic kidney disease (CKD). Research Design and Methods: Retrospective, nested case‐control study using data from national VA Corporate Data Warehouse. All adult patients with type 2 diabetes and CKD newly dispensed any antihyperglycaemic medication during FY 2003‐13 were included. The outcome was LA hospitalization or serum lactate >5 mEq/L. Exposure to metformin was evaluated in the three months prior to event. Estimates were adjusted for 31 covariates, including demographics, comorbidities and medications. Results: Overall, 320 882 patients were included, contributing a total of 1 331 784 person‐years of follow‐up. LA occurred in 2 665 patients, generating an overall incidence rate of 2.00 (95% CI 1.93‐2.08) per 1000 person‐years. Metformin exposure in the prior 3 months was associated with an elevated adjusted hazard of LA (HR 1.97, 95% CI 1.69‐2.29). No association was evident in patients with CKD stage 1 or 2 (HR 1.05, 95% CI 0.71‐1.57), but associations were present and progressively greater in patients with CKD stage 3a through 5: HR 3.09, 95% CI 2.19‐4.35 in CKD 3a, HR 3.34, 95% CI 1.95‐5.72 in CKD 3b, HR 7.87, 95% CI 3.51‐17.61 in CKD stage 4&5. Conclusion: Metformin was not associated with an elevated risk of LA in persons with stage 1‐2 CKD, but was associated with a progressively higher risk at more advanced stages of CKD. Abstract : Metformin was not associated with an elevated risk of LA in persons with stage 1‐2 CKD, but was associated with a progressively higher risk at more advanced stages of CKD.